Advances and perspectives in the metabolomics of stomatal movement and the disease triangle. (January 2021) - Xiang, Qingyuan; Lott, Aneirin A.; Assmann, Sarah M.; Chen, Sixue
Graphical abstract: Highlights: Metabolomics has facilitated studies of metabolites in stomatal disease triangle. Biotic and abiotic environmental factors regulate metabolites in stomatal immunity. Hormone signaling and crosstalk play important roles in stomatal immunity. Newly discovered metabolites have improved understanding of stomatal disease triangle. Emerging areas include single-cell metabolomics, multi-'omics and mass spectrometry imaging. Abstract: Crops are continuously exposed to microbial pathogens that cause tremendous yield losses worldwide. Stomatal pores formed by pairs of specialized guard cells in the leaf epidermis represent a major route of pathogen entry. Guard cells have an essential role as a first line of defense against pathogens. Metabolomics is an indispensable systems biology tool that has facilitated discovery and functional studies of metabolites that regulate stomatal movement in response to pathogens and other environmental factors. Guard cells, pathogens and environmental factors constitute the "stomatal disease triangle". The aim of this review is to highlight recent advances toward understanding the stomatal disease triangle in the context of newly discovered signaling molecules, hormone crosstalk, and consequent molecular changes that integrate pathogens and environmental sensing into stomatal immune responses. Future perspectives on emerging single-cell studies, multiomics and molecular imaging in the context of stomatal defense are discussed. Advances in this important area of plant biology will inform rational crop engineering and breeding for enhanced stomatal defense without disruption of other pathways that impact crop yield.